GHI Launch Des Moines 2012 - Ringler, Claudia (2012)
2012 Global Hunger Index Launch Event "The Challenge of Hunger: Ensuring Sustainable Food Security Under Land, Water & Energy Stresses" with Claudia Ringler October 18, 2012